Mapping endocrine networks by stable isotope tracing. (October 2022) - Andrew, Ruth; Stimson, Roland H.
Abstract: Hormones regulate metabolic homeostasis through interlinked dynamic networks of proteins and small molecular weight metabolites, and state-of-the-art chemical technologies have been developed to decipher these complex pathways. Stable-isotope tracers have largely replaced radiotracers to measure flux in humans, building on advances in nuclear magnetic resonance spectroscopy and mass spectrometry. These technologies are now being applied to localise molecules within tissues. Radiotracers are still highly valuable both preclinically and in 3D imaging by positron emission tomography. The coming of age of vibrational spectroscopy in conjunction with stable-isotope tracing offers detailed cellular insights to map complex biological processes. Together with computational modelling, these approaches are poised to coalesce into multi-modal platforms to provide hitherto inaccessible dynamic and spatial insights into endocrine signalling. Highlights: Stable isotope tracing is an exceptionally valuable tool to study metabolic flux in vivo in humans. Fluxomics can identify and quantify integrated endocrine pathways via tracking labels through multiple metabolic networks. Improved sensitivity and resolution of nuclear magnetic resonance spectroscopy and mass spectrometry, have enhanced the detection of labelled tracers. Spatial mapping of stable-isotope tracers in tissues and living cells can be achieved by mass spectrometry imaging and vibrational spectroscopy. Radiotracers combined with 3D imaging, such as positron emission tomography, offer high resolution with in vivo tracing.